2011
DOI: 10.1089/ars.2010.3698
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and Hemeproteins: Knowledge and Mysteries

Abstract: Historically, hydrogen sulfide (H(2)S) has been regarded as a poisonous gas, with a wide spectrum of toxic effects. However, like ·NO and CO, H(2)S is now referred to as a signaling gas involved in numerous physiological processes. The list of reports highlighting the physiological effects of H(2)S is rapidly expanding and several drug candidates are now being developed. As with ·NO and CO, not a single H(2)S target responsible for all the biological effects has been found till now. Nevertheless, it has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
142
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 83 publications
5
142
0
3
Order By: Relevance
“…Using exogenous H 2 S, we demonstrated that it promotes H 2 O 2 killing by specifically damaging heme-containing proteins, especially the CAT KatB, even though it is able to induce the protective OxyR regulon, as described in other bacterial species (3). Such an inhibitory effect on heme-containing proteins such as Cco (mitochondrial aa 3 type), myoglobin, and hemoglobin by H 2 S is well documented in eukaryotes (44)(45)(46). In general, the reaction between these proteins and H 2 S induced modification of the heme component, reversibly inhibiting activity (46,47).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Using exogenous H 2 S, we demonstrated that it promotes H 2 O 2 killing by specifically damaging heme-containing proteins, especially the CAT KatB, even though it is able to induce the protective OxyR regulon, as described in other bacterial species (3). Such an inhibitory effect on heme-containing proteins such as Cco (mitochondrial aa 3 type), myoglobin, and hemoglobin by H 2 S is well documented in eukaryotes (44)(45)(46). In general, the reaction between these proteins and H 2 S induced modification of the heme component, reversibly inhibiting activity (46,47).…”
Section: Discussionsupporting
confidence: 54%
“…Such an inhibitory effect on heme-containing proteins such as Cco (mitochondrial aa 3 type), myoglobin, and hemoglobin by H 2 S is well documented in eukaryotes (44)(45)(46). In general, the reaction between these proteins and H 2 S induced modification of the heme component, reversibly inhibiting activity (46,47). Sulfheme species, resulting from the binding of H 2 S, are reduced because of this interaction (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that [1] is in equilibrium with HS ⅐ -Fe II Hb [2]. The latter is also proposed as an intermediate for the sulfide-carrying Hb from L. pectinata (29), and its feasibility is supported by model studies showing that HS Ϫ ligation to ferric porphyrinate generates the corresponding Fe II derivative (30). In principle, the ferrous heme-bound HS ⅐ radical could react with O 2 to form SO 2 .…”
Section: Discussionmentioning
confidence: 83%